From Work-Life Conflict to Innovative Behaviour: The Mediating Roles of Psychological Capital, Leader-Member Exchange, and Resistance to Change - Dimas Dwi Utama; Zulfakhri Zulfakhri; Indah Nikensari; Tuty Sariwulan; Corry Yohana (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study examines how work life conflict affects innovative behaviour through psychological capital, leader member exchange, and resistance to change among telecommuting employees in an Indonesian general insurance company. The study responds to the growing relevance of flexible work, digital collaboration, and employee innovation in contemporary organisations. A quantitative explanatory design was employed using survey data from 211 permanent employees. The data were analysed using partial least squares structural equation modelling with SmartPLS. The results show that work life conflict negatively affects psychological capital, leader member exchange, and innovative behaviour, while positively affecting resistance to change. Psychological capital positively affects innovative behaviour and leader member exchange, while reducing resistance to change. Leader member exchange positively affects innovative behaviour and negatively affects resistance to change. Resistance to change negatively affects innovative behaviour. The mediation results confirm that psychological capital, leader member exchange, and resistance to change mediate the relationship between work life conflict and innovative behaviour. In addition, psychological capital and leader member exchange serially mediate this relationship. These findings indicate that employee innovation in telecommuting contexts is shaped by interconnected psychological, relational, and change related mechanisms. The study contributes to human resource management by highlighting the importance of reducing work life conflict, strengthening psychological capital, improving supervisor employee relationships, and managing resistance to change to sustain innovative behaviour.